2009
DOI: 10.15560/5.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Amphibia, Anura, Microhylidae, Hyophryne histrio: distribution extension

Abstract: None

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Three out of the 80 species recorded at RPPN Serra Bonita ( Eleutherodactylusbilineatus ”, Pristimantis paulodutrai , Pristimantis vinhai ) are endemic to the State of Bahia (Juncá and Pimenta 2004, Peixoto and Pimenta 2004a, Pimenta and Juncá 2004) and another six ( Adelophryne mucronatus , Brachycephalus pulex , Chiasmocleis crucis , Physalaemus camacan , Physalaemus erikae , Stereocyclops histrio and Scinax strigilatus ) are endemic to southern Bahia State (Cruz and Pimenta 2004, Pimenta et al 2005b, Pimenta et al 2007, Targino and Wild 2009, Napoli et al 2011a, Lourenço-de-Moraes et al 2012, Forlani et al 2013). Phyllodytes wuchereri and Dendropsophus novaisi are species known from less than three localities (Caramaschi et al 2004, Peixoto and Pimenta 2004b), whereas Bokermannohyla lucianae was only known from the municipality of Una (Dias et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Three out of the 80 species recorded at RPPN Serra Bonita ( Eleutherodactylusbilineatus ”, Pristimantis paulodutrai , Pristimantis vinhai ) are endemic to the State of Bahia (Juncá and Pimenta 2004, Peixoto and Pimenta 2004a, Pimenta and Juncá 2004) and another six ( Adelophryne mucronatus , Brachycephalus pulex , Chiasmocleis crucis , Physalaemus camacan , Physalaemus erikae , Stereocyclops histrio and Scinax strigilatus ) are endemic to southern Bahia State (Cruz and Pimenta 2004, Pimenta et al 2005b, Pimenta et al 2007, Targino and Wild 2009, Napoli et al 2011a, Lourenço-de-Moraes et al 2012, Forlani et al 2013). Phyllodytes wuchereri and Dendropsophus novaisi are species known from less than three localities (Caramaschi et al 2004, Peixoto and Pimenta 2004b), whereas Bokermannohyla lucianae was only known from the municipality of Una (Dias et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…One species of anuran was confirmed in the diet of post-metamorphic Ceratophrys aurita, the microhylid Hyophryne histrio (Targino and Wild, 2009). Although there has been a report of an additional anuran species, Trachycephalus cf.…”
Section: Ceratophrys Auritamentioning
confidence: 97%
“…To this, we add that seven individuals of Chiasmocleis sp. (snout-vent length [SVL] = 18.5-9.0 mm) were found (along with the single Hyophryne histrio of Targino and Wild, 2009) in the stomach of a single juvenile specimen (SVL = 55.3 mm) from Nova Viçosa municipality (17°52'S, 39°23'W) in the southern part of the State of Bahia, Brazil (MNRJ 19030). Dissection of this specimen and two additional individuals (MNRJ 19031, KU 92740) revealed that arthropods, especially ants (Formicidae) were the most commonly encountered prey (Tables 3 and 4).…”
Section: Ceratophrys Auritamentioning
confidence: 99%
“…The collection localities for H. histrio suggest that this species has a moderately large distributional range, since they encompass all South Bahia (see Targino and Wild, 2009). In at least one of these localities, Una, this species was locally abundant, with 42 specimens collected (Faria et al, 2007), while in the other localities the sample size is restricted to one specimen (Ilhéus, Itambé and Nova Viçosa).…”
Section: Distribution and Habitatmentioning
confidence: 99%
“…Hyophryne histrio is now known from four localities in the State of Bahia in northeastern Brazil: Ilhéus, the type-locality (Carvalho, 1954); Una (15 • 10 S, 39 • 31 W) (Dixo, 2004); Itambé (15 • 16 S, 40 • 27 W), the most inland record (Argôlo, 2005); and Nova Viçosa (17 • 52 S, 39 • 23 W), the southern-most record (map in Targino and Wild, 2009). Extensive sampling with pitfall traps with drift fences in Jussari and Uruçuca, (municipalities in State of Bahia), near Ilhéus and Una, where H. histrio is known to occur, did not produce H. histrio (Dixo, 2004).…”
Section: Distribution and Habitatmentioning
confidence: 99%